The Social Conditions of Regionalism in the Hungarian Balaton Region - Gergely Kabai (DETUROPE)
This paper shows the social conditions of Lake Balaton area. The first part presents the theoretical framework for the cohesion of society. The second part describes the processes that led to the complexity of local society in Lake Balaton area in the 20th century. Then, the paper presents the problems of cohesion about the society of Lake Balaton area. The author concludes that although there is a strong local cohesion in the society, but this phenomenon is geographically, dimensionally and thematically different in the area. All of this does not prevent the processes of bottom-up regionalization, which is a hundred years old phenomen in that area.